The role of bile acid in intestinal metaplasia - Wang, Menglei; Lou, Enzhe; Xue, Zengfu (Frontiers in Physiology, 2023)
A precancerous lesion of gastric cancer (GC), intestinal metaplasia (IM) is a pathological transformation of non-intestinal epithelium into an intestinal-like mucosa. It greatly raises the risk of developing the intestinal type of GC, which is frequently observed in the stomach and esophagus. It is understood that esophageal adenocarcinoma's precursor lesion, chronic gastroesophageal reflux disease (GERD), is what causes Barrett's esophagus (BE), an acquired condition (EAC). Recently, Bile acids (BAs), which is one of the compositions of gastric and duodenal contents, has been confirmed that it led to the occurrence and development of BE and GIM. The objective of thecurrent review is to discuss the mechanism of IM induced by bile acids. This review serves as a foundation for further research aimed at improving the way BE and GIM are currently managed.